Establishment and identification of an animal model of long-term exercise-induced fatigue - Yan, Kai; Gao, Haoyang; Liu, Xiaohua; Zhao, Zhonghan; Gao, Bo; Zhang, Lingli (Frontiers in Endocrinology, 2022)
In competitive sports, the training load is close to the human physiological limit, which will inevitably lead to exercise-induced fatigue. If fatigue cannot be recovered in time, it will eventually lead to excessive training and affect sport performance. Therefore, fatigue has become an important part of the physical function assessment for athletes. This paper will review animal models of long-term exercise-induced fatigue, modeling schemes of mice under treadmill and swimming training, phenotypes of long-term exercise-induced fatigue (e.g., nervous system damage, myocardial cell damage, bone mineral density changes, and skeletal muscle damage), and fatigue indicators. The relationship between physiological indicators and biomarkers and long-term exercise-induced fatigue is analyzed to promote exercise-induced fatigue monitoring. This paper attempts to provide a reference for the selection of animal models of long-term exercise-induced fatigue and provide a new theoretical basis for medical supervision and recovery of exercise-induced fatigue.